Coupled hydromechanical and electromagnetic disturbances in unsaturated porous materials. Issue 2 (4th February 2013) - Revil, A.; Mahardika, H.
Key Points First model built for unsaturated materials Basis for new methods to investigate the vadose zone All the material properties are related to measurable parameters